HUBUNGAN PERILAKU PENCEGAHAN DENGAN KEJADIAN MALARIA OLEH MASYARAKAT DI WILAYAH KERJA PUSKESMAS KALUMATA, SIKO DAN KALUMPANG KOTA TERNATE - Suni, Arsad (UPPM Politeknik Kesehatan Kemenkes Ternate, Maluku Utara, Indonesia, 2015)
Abstract : Malaria is the leading cause of death tropical diseases an estimated one million people in the worldwide die each year and new cases of malaria 200-300 million / year, and is one of the major public health problem because it affects morbidity infants, toddlers and maternal and give rise to extraordinary events. This study aims to examine the relationship behavior with the public about the prevention of malaria incidence in all three working areas of the health center. This study uses analytic approach to case control study, and the sampling technique is done by total sampling a total of 36 cases and 36 controls, and performed with the chi-square test with significance level α = 5% (0.05). The analysis showed a significant relationship between behavior modification with malaria incidence with a value of P = 0.002. there is a significant relationship between environmental modifications with malaria incidence with a value of P = 0.004. There was no significant relationship between the behavior of personal protection with malaria incidence with a value of P = 0.343. It was concluded that there was no significant relationship between the behavior of personal protection with the incidence of malaria, There is a significant relationship between behavior modification and modification of the environment with the incidence of malaria. Therefore, it is expected that the health centers regularly conduct counseling on malaria and prevention efforts.